Intravascular large B cell lymphoma presenting in the lung: the diagnostic value of transbronchial cryobiopsy - Poletti, Venerino; Gurioli, Carlo; Piciucchi, Sara; Rossi, Andrea; Ravaglia, Claudia; Dubini, Alessandra; Asioli, Silvia; Casoni, Gian Luca (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background and objective: intravascular large B-cell lymphoma is a distinct subtype of mature B-cell neoplasms, with uncommon primary presentation in the lungs. Diagnosis could be very difficult due to the lack of detectable tumor masses and it is usually made by surgical lung biopsy or autopsy examination. Methods: two patients occurred primarily with interstitial lung disease and underwent a pulmonary biopsy using cryoprobes. Results: the pathological analysis of the lung biopsies revealed in both cases a conclusive diagnosis of intravascular large B-cell lymphoma with primary lung involvement and patients have been safely diagnosed using transbronchial cryobiopsy for the first time in the literature. Conclusions: transbronchial cryobiopsy could be used as valid surrogate for surgical lung biopsy in lymphoprolipherative lung disorders (including intravascular lymphomas), as allows larger samples of tissue, greater  diagnostic yield, no crush artifacts and much less complications than surgical biopsy.